The routledge handbook of early christian art
1 online resource (422 pages)
Keywords: The Routledge Handbook of Early Christian Art surveys a broad spectrum of Christian art produced from the late second to the sixth centuries. The first part of the book opens with a general survey of the subject and then presents fifteen essays that discuss specific media of visual art—catacomb paintings, sculpture, mosaics, gold glass, gems, reliquaries, ceramics, icons, ivories, textiles, silver, and illuminated manuscripts. Each is written by a noted expert in the field. The second part of the book takes up themes relevant to the study of early Christian art. These seven chapters consider the ritual practices in decorated spaces, the emergence of images of Christ’s Passion and miracles, the functions of Christian secular portraits, the exemplary mosaics of Ravenna, the early modern history of Christian art and archaeology studies, and further reflection on this field called “early Christian art.” Each of the volume’s chapters includes photographs of many of the objects discussed, plus bibliographic notes and recommendations for further reading.